Nutrition promotion and collective vegetable gardening by adolescent girls: Feasibility assessment from a pilot in Afghanistan - Alim, Md. Abdul; Hossain, M. Anowar (AESS, 2022)
This article was published in The Asian Journal of Agriculture and Rural Development [©2018 Published by Asian Economic and Social Society] and the definite version is available at: http://doi:10.18488/journal.1005/2018.8.1/1005.1.40.49 The Article's website is at: http://59.160.153.187/sites/default/files/NUTRITION%20PROMOTION%20AND%20COLLECTIVE%20VEGETABLE%20GARDENING.pdf